Characteristics of edible film from chitosan as biodegradable packaging. Issue 1 (March 2021) - Saputra, E; Tjahjaningsih, W; Abdillah, A A
Abstract: This research aimed to study the capability of CMC in improving the characteristics of an edible film made from chitosan, as well as to see the ability of edible film in maintaining the shelf life of fish burger product at room temperature. Three various concentration of CMC was used, namely 0.1%, 0.3% and 0.5%. The results of chitosan edible film characterization from the three concentrations of CMC showed that the concentration of 0.1% was the best as a plasticizer, with thickness 0.19 mm, water vapor transmission rate 50.8 ml/m 2 /day, the tensile strength 24.2 kgf/cm 2, and percentage elongation 18.1%.